PENGARUH PEMAMFAATAN SARANA BELAJAR DI SEKOLAH, MINAT, DAN DISIPLIN TERHADAP HASIL BELAJAR - Apriadi Widodo Simamora; Yon Rizal; Tedi Rusman (FKIP Unila, 2015)
This study aimed to determine the effect of learning tool utilization in schools, interest in learning, and learning discipline to the learning outcomes of integrated social studies of class VIII SMP Negeri 2 Ketapang in the academic year 2013/2014. This research method was using descriptive approach verification of ex post pacto and surveys. Sampling techniques with non probability sampling with sampling saturated kind. To test hypothesis using Product Moment Correlation and Multiple. Based on data analysis, it obtaireds: (1) There is a positive influence on the utilization of learning tool in schools on learning outcomes of Integrated Social Science, (2) There is a positive influence on interest in learning on the learning outcomes of integrated social science. (3) There is a positive influence on the discipline of learning to the learning outcomes of Integrated Social Science. (4) There is a positive influence of the utilization of learning tool in school, learning interest and learning discipline of integrated social learning outcomes.Penelitian ini bertujuan mengetahui pengaruh pemanfaatan sarana belajar di sekolah, minat belajar, dan disiplin belajar terhadap hasil belajar pelajaran IPS terpadu siswa kelas VIII SMP Negeri 2 Ketapang tahun pelajaran 2013/2014. Metode penelitian ini menggunakan deskriptif verifikatif dengan pendekatan ex post facto dan survei. Teknik sampling dengan non probability sampling dengan jenis sampling jenuh. Untuk menguji hipotesis menggunakan Korelasi Product Moment dan Multiple. Berdasarkan analisis data diperoleh : (1) Ada pengaruh positif pemanfaatan sarana belajar di sekolah terhadap hasil belajar IPS Terpadu, (2) Ada pengaruh positif minat belajar terhadap hasil belajar IPS Terpadu, (3) Ada pengaruh positif disiplin belajar terhadap hasil belajar IPS Terpadu, (4) Ada pengaruh positif Pemamfaatan Sarana Belajar di Sekolah,Minat Belajar dan Disiplin Belajar terhadap hasil belajar IPS Terpadu.Kata kunci: pemamfaatan sarana belajar di sekolah, minat belajar, disiplin belajar, IPS terpadu